Employee workplace wellbeing: the blind spot of the financial industry - Harter, Benjamin Philipp (2024)
Mental health related disorders have been rising steadily in the past years, accelerated by the Covid-19 pandemic. Especially younger generations reported the strongest decline in terms of their mental health (Global Mind Project, 2024). In Germany, €24.3bn of gross value added are lost due to the cost of incapacity of work because of mental health related issues. However, a large share of employees believes that companies and leadership were still not concerned about their wellbeing. Therefore, the study aims to better understand, based on a qualitative method in form of semi-structured interviews, how workplace related EWB, and in particular mental health issues, unfold in the Financial Industry and further to apply the concept of HoL as an important contributing factor. The concept of health-oriented leadership emerged in the literature as a criticism of general leadership theories and to specifically address the topic of health in organizations. The study is based in the German Financial Industry. Throughout the process of 14 qualitative one-on-one semi structured interviews, two global themes, namely EWB in the Financial Industry, and Leadership behavior and EWB were identified by the researcher. The study contributes to the literature by linking the concept of health-oriented leadership specifically to the Financial Industry offering new potential conceptualizations and providing a state-of-the-art assessment on EWB in the Financial Industry. From a managerial side, insights into policy and practice are provided to foster EWB inside organizations.